Mitsugumin 53 (MG53) ligase ubiquitinates focal adhesion kinase during skeletal myogenesis - Nguyễn, Thị Huỳnh Nga (2022)
The striated muscle-specific mitsugumin 53 (MG53) is a novel E3 ligase that induces the ubiquitination of insulin receptor substrate 1 (IRS-1) during skeletal myogenesis, negatively regulating insulin-like growth factor and insulin signaling. Here we show that focal adhesion kinase (FAK) is the second target of MG53 during skeletal myogenesis. The FAK protein level gradually decreased, whereas its mRNA level was constant during myogenesis in C2C12 cells and MyoD-overexpressing mouse embryonic fibroblasts. The FAK protein was associated with the E2 enzyme UBE2H and the E3 enzyme MG53 in endogenous and exogenous immunoprecipitation experiments. FAK ubiquitination and degradation was induced by MG53 overexpression in myoblasts but abolished by MG53 or UBE2H knockdown in myotubes. Because RING-disrupted MG53 mutants (C14A and ΔR) did not induce FAK ubiquitination and degradation, the RING domain was determined to be required for MG53-induced FAK ubiquitination. Taken together, these data indicate that MG53 induces FAK ubiquitination with the aid of UBE2H during skeletal myogenesis.